Spatial Engineering of Mammary Epithelial Cell Cultures with 3D Bioprinting Reveals Growth Control by Branch Point Proximity - Koskinen, Leena M. (Springer Nature, 2025)
The three-dimensional (3D) structure of the ductal epithelium and the surrounding extracellular matrix (ECM) are integral aspects of the breast tissue, and they have important roles during mammary gland development, function and malignancy. However, the architecture of the branched mammary epithelial network is poorly recapitulated in the current in vitro models. 3D bioprinting is an emerging approach to improve tissue-mimicry in cell culture. Here, we developed and optimized a protocol for 3D bioprinting of normal and cancerous mammary epithelial cells into a branched Y-shape to study the role of cell positioning in the regulation of cell proliferation and invasion. Non-cancerous cells formed continuous 3D cell networks with several organotypic features, whereas the ductal carcinoma in situ (DCIS) –like cancer cells exhibited aberrant basal polarization and defective formation of the basement membrane (BM). Quantitative analysis over time demonstrated that both normal and cancerous cells proliferate more at the branch tips compared to the trunk region of the 3D-bioprinted cultures, and particularly at the tip further away from the branch point. The location-specific rate of proliferation was independent of TGFβ signaling but invasion of the DCIS-like breast cancer cells was reduced upon the inhibition of TGFβ. Thus, our data demonstrate that the 3D-bioprinted cells can sense their position in the branched network of cells and proliferate at the tips, thus recapitulating this feature of mammary epithelial branching morphogenesis. In all, our results demonstrate the capacity of the developed 3D bioprinting method for quantitative analysis of the relationships between tissue structure and cell behavior in breast morphogenesis and cancer.